Sebaran Bukit Karst Di Wilayah Kabupaten Sijunjung - Nofirman Nofirman (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2017)
Phenomenon of Hill karst have the characteristic with the characteristic predominated by limestone contain the calcite and dolomit. This rock have a lot of usefulness and its benefit. Strive to identify the swampy forest of hill karst conducted by using image from application SAS.PLANET.RELEASE.160707. Visible of Area of hill karst and its dale can be perceived better at image, so that earn the confirmation with the field condition. Area of Hill karst in Region of Regency of Sijunjung visible enough vary to start from there are; permanent wellspring, dolin, uvala, polje, lake, underground river, speleotem, and aquifer, up to area karst which visiblelity have been closed by thick sediment coat. Phenomenon of resident Life in region Sijunjung which still predominate by primary sector. Needed approach empowermant to be they interaction can environmentally ecosystem functionally.Phenomenon of Hill karst have the characteristic with the characteristic predominated by limestone contain the calcite and dolomit. This rock have a lot of usefulness and its benefit. Strive to identify the swampy forest of hill karst conducted by using image from application SAS.PLANET.RELEASE.160707. Visible of Area of hill karst and its dale can be perceived better at image, so that earn the confirmation with the field condition. Area of Hill karst in Region of Regency of Sijunjung visible enough vary to start from there are; permanent wellspring, dolin, uvala, polje, lake, underground river, speleotem, and aquifer, up to area karst which visiblelity have been closed by thick sediment coat. Phenomenon of resident Life in region Sijunjung which still predominate by primary sector. Needed approach empowermant to be they interaction can environmentally ecosystem functionally.